Analisis Implementasi Program Kartu Jakarta Mahasiswa Unggul (KJMU) di DKI Jakarta - Iqbal Fikri Nurprastya; Puji Astuti (Journal of Politic and Government Studies, 2026)
The Kartu Jakarta Mahasiswa Unggul (KJMU) program is an educational policy intervention by the Provincial Government of DKI Jakarta aimed at democratizing access to higher education for underprivileged citizens. This study aims to analyze the implementation effectiveness of the KJMU program following the enactment of Governor Regulation Number 101 of 2021 and to evaluate its governance. This study employs a descriptive qualitative approach. Data were collected through in-depth interviews with officials from the Center for Personal and Operational Education Funding Services (P4OP) and recipient students from various universities (UNJ, UIN Syarif Hidayatullah Jakarta, UPN Veteran Jakarta), supported by secondary data triangulation. The analysis is constructed using the implementation theories of Van Meter and Van Horn, Mazmanian and Sabatier, alongside the concept of Good Public Policy Governance. The findings indicate that: (1) The transition of quantitative welfare measurement using the Integrated Social Welfare Data (DTKS) successfully improved accountability and suppressed inclusion errors; however, its implementation is trapped in the pathology of bureaucratic fragmentation (Silo Effect) among P4OP, the Social Agency, and Bappenda, which slows down public services; (2) There is a deficit in preventive information transparency that triggered unilateral termination of participation (shock implementation), thereby spawning social innovation in the form of Target Group Resilience through the movement of informal campus actors (NaraMuda and Forum KJMU communities) to break through the bureaucratic deadlock; (3) At the outcome level, KJMU funds are proven to be highly effective acting as a "cognitive liberator" that eliminates both direct and indirect educational cost barriers. To suppress the bureaucratic pathology, the researcher recommends the establishment of a Single Window System based on cross-agency data interoperability, regulatory amendments accommodating a grace period, and host to-host digitalization of academic verification.